Biological activities of extracts from Chenopodium ambrosioides Lineu and Kielmeyera neglecta Saddi - Sousa Zulane; de Oliveira Fernando; da Conceição Aline; Silva Luiz Alberto; Rossi Maria; Santos Juliana da; Andrioli João (BMC, 2012)
Abstract Background Chenopodium ambrosioides and Kielmeyera neglecta are plants traditionally used in Brazil to treat various infectious diseases. The study of the biological activities of these plants is of great importance for the detection of biologically active compounds. Methods Extracts from these plants were extracted with hexane (Hex), dichloromethane (DCM), ethyl acetate (EtOAc) and ethanol (EtOH) and assessed for their antimicrobial properties, bioactivity against Artemia salina Leach and antifungal action on the cell wall of Neurospora crassa. Results Extracts from C. ambrosioides (Hex, DCM and EtOH) and K. neglecta (EtOAc and EtOH) showed high bioactivity against A. salina (LD50 < 1000 μg/mL), which might be associated with cytotoxic activity against cancer cells. C. ambrosioides Hex and DCM showed specific activity against yeasts, highlighting the activity of hexanic extract against Candida krusei (MIC = 100 μg/mL). By comparing the inhibitory concentration of 50% growth (IC 50%) with the growth control, extracts from K. neglecta EtOAc and EtOH have shown activities against multidrug-resistant bacteria (Enterococcus faecalis ATCC 51299 and Staphylococcus aureus ATCC 43300), with IC 50% of 12.5 μg/mL The assay carried out on N. crassa allowed defining that extracts with antifungal activity do not have action through inhibition of cell wall synthesis. Conclusions Generally speaking, extracts from C. ambrosioides and K. neglecta showed biological activities that have made the search for bioactive substances in these plants more attractive, illustrating the success of their use in the Brazilian folk medicine.